2009
DOI: 10.1021/ef900127z
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization Behavior of Iron-based Sorbent with MgO and TiO2Additive in Hot Coal Gas

Abstract: The sulfidation behaviors of iron-based sorbent with MgO and MgO-TiO2 are studied under different isothermal conditions from 623 to 873 K in a fixed bed reactor. The results of sorbents sulfidation experiments indicate that the sorbents with MgO and TiO2 additives are more attractive than those without additives for desulfurization of hot coal gas. The sulfur capacity (16.17, 18.45, and 19.68 g S/100 g sorbent) of M1F, M3F, and M5F sorbent containing 1, 3, and 5% MgO, respectively, is obviously bigger than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Similar competitive adsorption has been reported for ZnO (Novochinskii et al, 2004;Fan et al, 2003). Type B sites would exclusively take up H 2 S reversibly, involving the formation of a metal sulphide (Toops and Crocker, 2008;Bao et al, 2009). The metal sulphide would be formed from the metal oxide at H 2 S-rich conditions, while the presence of steam and the absence of H 2 S during regeneration would result in partial backformation of the metal oxide and release of H 2 S according to the following reaction equation:…”
Section: Resultsmentioning
confidence: 99%
“…Similar competitive adsorption has been reported for ZnO (Novochinskii et al, 2004;Fan et al, 2003). Type B sites would exclusively take up H 2 S reversibly, involving the formation of a metal sulphide (Toops and Crocker, 2008;Bao et al, 2009). The metal sulphide would be formed from the metal oxide at H 2 S-rich conditions, while the presence of steam and the absence of H 2 S during regeneration would result in partial backformation of the metal oxide and release of H 2 S according to the following reaction equation:…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23] Thus, it is possible that limonite-derived α-Fe will be a good adsorbent for H 2 S in COG. However, only a few studies have reported H 2 S removal in COG by iron-based adsorbents, such as iron oxide and/or iron-bearing sorbents combined with other metals.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, there were many investigations of single metal oxide and mixed metal oxides as sorbents in the past [7][8][9][10][11]. And iron oxide has become the study focus for advantages of low cost, high sulfurization rate, good regeneration ability and superior sulfur capacity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%